Transition Metals-Based Water Splitting Electrocatalysts on Copper-Based Substrates: The Integral Role of Morphological Properties - Selvanathan S.; Meng Woi P.; Selvanathan V.; Karim M.R.; Sopian K.; Akhtaruzzaman M. (John Wiley and Sons Inc, 2025)
Electrocatalytic water splitting is a promising alternative to produce high purity hydrogen gas as the green substitute for renewable energy. Thus, development of electrocatalysts for both hydrogen evolution reaction (HER) and oxygen evolution reaction (OER) are vital to improve the efficiency of the water splitting process particularly based on transition metals which has been explored extensively to replace the highly active electrocatalytic activity of the iridium and ruthenium metals-based electrocatalysts. In situ growth of the material on a conductive substrate has also been proven to have the capability to lower down the overpotential value significantly. On top of that, the presence of substrate has given a massive impact on the morphology of the electrocatalyst. Among the conductive substrates that have been widely explored in the field of electrochemistry are the copper based substrates mainly copper foam, copper foil and copper mesh. Copper-based substrates possess unique properties such as low in cost, high tensile strength, excellent conductor of heat and electricity, ultraporous with well-integrated hierarchical structure and non-corrosive in nature. In this review, the recent advancements of HER and OER electrocatalysts grown on copper-based substrates has been critically discussed, focusing on their morphology, design, and preparation methods of the nanoarrays. ? 2023 The Chemical Society of Japan & Wiley-VCH GmbH.